Trends Shaping the Future: Economic, Societal, and Environmental Trends. - Cetron, Marvin J.; Davies, Owen (Futurist)
As an update to the special report published by the World Future Society in 2001, the writers examine key trends that are shaping the world of the next two decades and beyond. These patterns have been tracked for four decades by the writers, Forecasting International Ltd. president Marvin J. Cetron and his longtime collaborator, science writer Owen Davies. This article focuses on general economic trends, social and demographic changes, and trends in energy and the environment.